2014
DOI: 10.4049/jimmunol.1400288
|View full text |Cite
|
Sign up to set email alerts
|

KIR/HLA Interactions Negatively Affect Rituximab- but Not GA101 (Obinutuzumab)-Induced Antibody-Dependent Cellular Cytotoxicity

Abstract: Ab-dependent cellular cytotoxicity (ADCC) mediated by NK cells is regulated by inhibitory killer cell Ig–like receptors (KIRs), which interact with target cell HLA class I. We analyzed how KIR/HLA interactions influence ADCC induced by rituximab and by GA101, a novel type II CD20 Ab glycoengineered for increased FcgRIII binding and ADCC capacity. We found that KIR/HLA interactions strongly and selectively inhibit rituximab-induced in vitro ADCC toward target cells expressing cognate HLA KIR ligands. NK cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 27 publications
6
60
0
Order By: Relevance
“…Importantly, multiple KIR/HLA interactions were necessary to decrease obinutuzumabinduced ADCC to the level achieved by rituximab. 2 In line with these observations, target depletion was unaffected by both the percentage of unlicensed effector cells in the repertoire, and by the number of KIR ligands expressed on target cells. In summary, obinutuzumab can induce comparable percentage and quality of activation in all NK cells subpopulations, independent from the licensing status and the KIR/HLA interactions (Fig.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Importantly, multiple KIR/HLA interactions were necessary to decrease obinutuzumabinduced ADCC to the level achieved by rituximab. 2 In line with these observations, target depletion was unaffected by both the percentage of unlicensed effector cells in the repertoire, and by the number of KIR ligands expressed on target cells. In summary, obinutuzumab can induce comparable percentage and quality of activation in all NK cells subpopulations, independent from the licensing status and the KIR/HLA interactions (Fig.…”
supporting
confidence: 67%
“…1A). 2 In line with the concept of unlicensed NK cells being the strongest ADCC effector cells, we observed that killing efficiency correlated positively with the percentage of unlicensed cells. Considering that in Caucasians approximately 30 percent of individuals carry all HLA ligands to the 3 relevant inhibitory KIR receptors (KIR2DL1, KIR2DL2/3, and KIR3DL1), the benefit of anti-CD20 therapy in such patients may be strongly limited by NK cell tolerance.…”
supporting
confidence: 66%
“…We limited our analysis to 2DL1-3 and 3DL1 based on the recently reported involvement of these KIRs on efficacy of Ab-dependent immunotherapy. 7,28 Due to lack of expression on effector cells, we excluded the remaining known KIR pseudogenes 2DP1and 3DP1 from our analysis. 29 For analysis of KIRLs HLA-C1, HLA-C2 and HLA-Bw4, DNA samples of 52 NB patients were available.…”
Section: Frequency Of Distinct Kir/kirl Genotypes Of Treated Neuroblamentioning
confidence: 99%
“…Following treatment protocol was used: cytokine IL-2 was given for 5 d (s.c., day 1-5, 6 £ 10 6 IU/m 2 /day), followed by a combined application of IL-2 (s.c., day 8-12, 6 £ 10 6 IU/m 2 / day) with ch14.18/CHO (i.v., day 8-18, 10 mg/m 2 /day) and 13-cis-retinoic acid (p.o., day [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. At initial diagnosis, 46 patients had stage 4, four stage 3, one stage 2 and two stage 1 disease.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…43 In particular, obinutuzumab has a 50-fold higher affinity for the FcgRIIIa region and 100-fold greater ADCC than rituximab. 43,49 It also has no CD20 antigen internalization with binding, and thus no shaving/trogocytosis in contrast to rituximab. 43 The CLL 11 study conducted by the GCLLSG was recently published in the New England Journal of Medicine (NEJM).…”
Section: Nahas and Arnasonmentioning
confidence: 99%